The Implementation of the Professional Role of the Community Pharmacist in the Immunization Practices in Italy to Counteract Vaccine Hesitancy - Rosagemma Ciliberti; Nicola Luigi Bragazzi; Alessandro Bonsignore (MDPI AG, 2020)
In Italy, the National Vaccinal Prevention Plan has renewed the commitment of the Italian government to promote a culture of vaccination practices in the general population and especially among healthcare professionals, considering it as a strategic goal. The search for useful tools and techniques to promote a layered and widespread information network capable of restoring a climate of trust and confidence towards vaccination, leads us to reflect on the possibility, already adopted in numerous countries, of enlisting community pharmacies in immunization campaigns also in Italy, positively implementing the professional role of the community pharmacist in immunization. The pharmacist is often the first point of contact with both the patients and the public, both for the relationship of trust and confidence that binds him to the citizens, and for the ease of access in relation to the widespread distribution of community pharmacies in the territory, the availability of prolonged operating hours, the absence of need for appointments and positions near/outside of healthcare facilities. Currently, in Italy the role of the community pharmacist is limited to counseling and providing advice and information regarding the benefits and/or any risks of vaccination practices, but does not imply a direct engagement in immunization programs, rather a collaboration to avoid straining and overwhelming the vaccination centers. Some recent questionnaire-based studies have shown that Italian community pharmacists have attitudes that are favorable to vaccinations, even though their knowledge is rather limited. Together with expanding the engagement of community pharmacists in immunization programs, their educational gap should be addressed in order to significantly improve and enhance the protection of the public health.